Compensation of London Dispersion in the Gas Phase and in Aprotic Solvents. Issue 40 (30th August 2019) - Pollice, Robert; Fleckenstein, Felix; Shenderovich, Ilya; Chen, Peter
Abstract: The importance of London dispersion for structure and stability of molecules with less than about 200 atoms has been established in recent years but the quantitative understanding is still largely based on computations because of a persistent lack of suitable experimental data. We herein report a comprehensive computational and experimental study of the compensation of London dispersion in proton‐bound dimer dissociations showing that total compensation is largely invariant in both polar and nonpolar aprotic solvents spanning a wide range of bulk polarizabilities. Additionally, we find that compensation by solvent (which is about 40–80 %) largely dominates over compensation in the gas phase (which is about 0–40 %) for typical experimental temperatures. Abstract : Quid pro quo : London dispersion forces are compensated significantly in solution relative to the gas phase at absolute zero. At ambient temperatures, the largest contribution of total compensation stems from solvation; gas‐phase entropy is a minor but still important component. The extent of total compensation in solution is largely independent of solvent bulk polarizability.